Answer:
422455.41
Explanation:
Corrected from source,
Given that:-
[tex]N2(g) + 3 H2(g)\rightarrow 2NH3(g) \ Kc_1 = 0.314[/tex]
The equilibrium constant for the reverse reaction will be the reciprocal of the initial reaction.
The value of equilibrium constant the reaction
[tex]2NH3(g)\rightarrow N2(g) + 3 H2(g)[/tex]
is:
[tex]Kc_{1}'=\frac{1}{0.314}[/tex]
[tex]H2(g) + I2(g)\rightarrow 2 HI(g)\ Kc_2 = 51[/tex]
If the equation is multiplied by a factor of '3', the equilibrium constant of the reverse reaction will be the cube of the equilibrium constant of initial reaction.
The value of equilibrium constant the reaction
[tex]3H2(g) + 3I2(g)\rightarrow 6 HI(g)[/tex]
is:
[tex]Kc_{2}'={51}^3[/tex]
Adding both the reactions we get the final reaction. So, the equilibrium constants must be multiplied.
The value of equilibrium constant the reaction
[tex]2NH3(g) + 3I2(g)\rightarrow 6 HI(g) + N2(g)[/tex]
is:
[tex]Kc'=\frac{1}{0.314}\times {51}^3[/tex] = 422455.41